A semi-empirical relation based on temperature difference and filling ratio in a closed loop pulsating heat pipe: A numerical study. - Vasanth Balamurugan; Shahid Mian P; Md Jahid Hasan; Natteri M Sudharsan (PLoS ONE)
A closed-loop pulsating heat pipe (CLPHP) is an attractive passive cooling system for electronic components. The design of CLPHP is challenging due to the complex nature of thermo-hydrodynamic coupling. This study investigates the heat transfer efficiency of a CLPHP using water as the working fluid. The heat transfer rate is evaluated for a volume fraction of 0.3-0.7 and an evaporator temperature of 323-373 K. From the computed results, a regression analysis is performed to generate a semi-empirical equation. The empirical relation for heat transfer rate (Q) as a function of the temperature difference and filling ratio was found to match the CFD results. Similarly, a semi-empirical equation for heat flux (q) as a function of non-dimensionless numbers is presented to calculate the heat transfer rate (Q) for various filling ratios, and found to match CFD results. A force plot measuring the net force acting on the slugs is presented for various filling ratios and evaporator temperatures. The net force plot will help optimize the design of the CLPHP and improve its efficiency. When comparing slug formation pulsatile cycle and thermal efficiency, 0.5 volume fraction was found to be optimum. For this filling ratio (0.5) heat transfer rate is enhanced from 40% to 86% when the evaporator temperature is increased by 15%.